Specific Ion Effects at the Vapor-Formamide Interface A Reverse Hofmeister Series in Ion Concentration Depth Profiles - Kumar, Anand (Langmuir : the ACS journal of surfaces and colloids, 2023)
Employing neutral impact collision ion scattering spectroscopy (NICISS), we have directly measured the concentration depth profiles (CDPs) of various monovalent ions at the vapor-formamide interface. NICISS provides CDPs of individual ions by measuring the energy loss of neutral helium atoms backscattered from the solution interface. CDPs at the vapor-formamide interface of Cl-, Br-, I-, Na+, K+, and Cs+ are measured and compared to elucidate the interfacial specific ion trends. We report a reverse Hofmeister series in the presence of inorganic ions (anion and cation) at the vapor-formamide interface relative to the water-vapor interface, and the CDPs are found to be independent of the counterion for most ions studied. Thus, ions at the surface of formamide follow a "Hofmeister paradigm" where the counterion does not impact the ion series. These specific ion trends are complemented with surface tension and X-ray absorption near-edge structure (XANES) measurements on formamide electrolyte solutions